Analisis Alterasi dan Mineralisasi pada Endapan Bijih di Daerah Reboya, Kecamatan Taliwang, Kabupaten Sumbawa Barat - Aji Syailendra Ubaidillah (Universitas Nasional, 2026)
Sumbawa Island is the part of a magmatic arc system with significant potential for sulfide mineralization. This study aims to identify the characteristics of hydrothermal alteration, mineralization, and the type of hydrothermal deposit occurring at Mount Reboya, Telaga Bertong Village, Taliwang District, West Sumbawa Regency. The research methods included geological field observations, rock sampling, and megascopic and petrographic analyses. The results reveal the presence of alteration minerals, including plagioclase, K-feldspar, quartz, biotite, hornblende, and clay minerals, which are associated with argillic, advanced argillic, silicification, and potassic alteration types. Ore minerals identified in the study area consist of pyrite, chalcopyrite, sphalerite, and galena. Based on the mineral assemblages and alteration characteristics, the hydrothermal deposits developed in the study area are interpreted to be of epithermal and hypothermal types. This study provides insights into the hydrothermal processes that have affected the area and offers a scientific basis for further mineral exploration activities.